DIFFERENCES IN INTERMITTENT AND CONTINUOUS PHOTOTHERAPY ADMINISTRATION ON BILIRUBIN LEVELS IN NEONATAL JAUNDICE IN THE PERINATOLOGY ROOM, BRAWIJAYA UNIVERSITY HOSPITAL, MALANG - Nery Agustin; Sulistiyah (Journal of Public Health Science, 2026)
Neonatal jaundice is a common condition in newborns caused by elevated bilirubin levels due to immature liver function. Phototherapy is the primary treatment to reduce bilirubin levels and can be administered intermittently or continuously. This study aimed to compare the effectiveness of intermittent and continuous phototherapy in reducing bilirubin levels among neonates with jaundice in the Perinatology Ward of Brawijaya University Hospital, Malang. This study employed a quasi-experimental design using a non-equivalent control group design. The sample consisted of 30 neonates, with 15 assigned to the intermittent phototherapy group and 15 to the continuous phototherapy group. Data were analyzed using the Shapiro–Wilk normality test, Paired Sample t-test, and Mann–Whitney test. The mean bilirubin level in the intermittent phototherapy group decreased from 15.82 mg/dL before the intervention to 10.94 mg/dL after the intervention, while the continuous phototherapy group showed a decrease from 15.67 mg/dL to 10.61 mg/dL. Both intermittent and continuous phototherapy significantly reduced bilirubin levels after treatment. However, there was no statistically significant difference in effectiveness between the two methods based on the Mann–Whitney test (p = 0.713). In conclusion, intermittent and continuous phototherapy are equally effective in reducing bilirubin levels in neonates with jaundice and may be selected according to the neonate's clinical condition and hospital policy..